Importancia de la gestión institucional para el rescate de la identidad cultural de los estudiantes de la Unidad Educativa a distancia Monseñor Leonídas Proaño de la ciudad de Pujilí - Pillisa Sangucho, Luis Fabián (2016)
This research aims to make aware the educational community about the importance of rescuing the cultural roots of each person, thus promoting respect and love for the diversity of cultures that Ecuador has. It has been detected in the Institution loss of cultural identity in young students which is a problem that affects to maintain good social and cultural integration, analytical and thoughtful critical analysis was performed to determine the causes that carry out to loss of identity of student. Surveys and direct observation were made and applied to students parents, principals and teachers of the educational unit….